SOCIALIZATION OF THE IMPACT OF SWITCHING FACINING FOR FOREST ECOSYSTEMS IN IMABATAI VILLAGE, INAMOSOL SUB-DISTRICT, WEST SERAM DISTRICT - M. Matinahoru, Johan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The people of Imabatai village live in the Nuduasiwa customary forest group and 45 heads of families work as farmers who practice the shifting farming system. The average area of shifting cultivation carried out is 0.3 ha / KK / year. This means that there is damage to the forest ecosystem of 13.5 ha / year. The purpose of this service activity is to increase farmers' understanding of the impact of shifting farming practices on the destruction of forest ecosystems. This counseling activity succeeded in increasing the understanding of Imabatai village farmers by 80% (36 heads of families were able to understand the impact of shifting farming practices).